Effects of Social Capital and Leisure Participation on Self-Rated Health of Urban Residents in Southwest China - XiaoYan Hu; MingWen Hu (Frontiers Media S.A., 2021)
Background: Leisure provides opportunities for urban and rural residents to relax, recover their vitality, and improve their personal growth, development, and well-being. However, the impact of the leisure participation process, types, obstacles, participation motivation, and satisfaction on health is not very clear, especially the impact of leisure behavior on health, and is worthy of in-depth discussion.Objective: The objective of this study was to explore the impact of social capital and leisure participation on the self-rated health of urban residents in China so as to provide an important reference for national health promotion activities.Methods: the questionnaire on the relationship between social capital, leisure behavior, and self-rated health was compiled by ourselves. The residents participating in leisure and fitness in 25 residential fitness centers in Chengdu were investigated in the morning and evening, and the obtained data were processed by exploratory and confirmatory factor analysis.Results: (1) Social capital had no direct influence on leisure hindrance; leisure motivation and leisure participation had no direct influence on self-rated health. (2) Leisure satisfaction has a direct positive impact on self-rated health, while leisure hindrance has a significant negative impact on self-rated health. (3) Social capital has a direct positive impact on leisure satisfaction, and social capital has a direct positive impact on self-rated health. Leisure satisfaction plays an intermediary role in the path of social capital affecting self-rated health, and the intermediary force exceeds the direct impact of social capital on self-rated health.Conclusion: The effect of leisure satisfaction on self-rated health is higher than that of social capital, and it plays an intermediary role in the impact path of social capital on self-rated health. Therefore, how to make urban community residents with different backgrounds obtain leisure satisfaction through leisure activities is an important topic of national health promotion.